URGENSI PENANAMAN KARAKTER DALAM KELUARGA TERHADAP PEMBENTUKAN KONSEP DIRI REMAJA - Nurun Nida Waddiny; Taufik Hidayat (Al Arsy: Journal of Education, Management and Islamic Thought, 2025)
The family is the smallest social unit that plays a fundamental role as the first and foremost educational institution in the process of shaping children's personalities and characters. However, in this modern era, globalization and advances in digital technology have triggered a shift in traditional values, leading to a decline in empathy and a weakening of character among the younger generation. This study aims to analyze the urgency of instilling character values in the family as the main foundation in the process of shaping adolescents' self-concept, as well as to explain how certain parenting methods can build their moral awareness. This study uses a qualitative approach with a literature study method that systematically analyzes various scientific literature, official documents, and related journals. The results show that instilling character through habituation, affection, and role modeling is very effective in building moral awareness.